Disseminated Intravascular Coagulation Complicating the Conservative Management of Placenta Percreta. Issue 5 (November 2015) - Judy, Amy E.; Lyell, Deirdre J.; Druzin, Maurice L.; Dorigo, Oliver
Abstract : BACKGROUND: Retention of the placenta is an option in the management of placenta percreta; however, it may be associated with significant morbidity. CASE: We present a case of conservative management of placenta percreta. Disseminated intravascular coagulation (DIC) developed 49 days after delivery. An urgent hysterectomy was performed, followed by rapid normalization of coagulation parameters. CONCLUSION: Disseminated intravascular coagulation may complicate the conservative management of placenta percreta and can manifest weeks after delivery in the absence of antecedent hemorrhage or infection. The time course and presentation of this case are similar to the development of DIC after prolonged retention of a fetal demise with a probable shared pathophysiology. Close follow-up may facilitate prompt diagnosis of DIC, thereby minimizing associated morbidity. Abstract : Disseminated intravascular coagulation is a potential complication of the conservative management of placenta percreta.